Targeted separation of antibacterial peptide from protein hydrolysate of anchovy cooking wastewater by equilibrium dialysis. (1st February 2015) - Tang, Wenting; Zhang, Hui; Wang, Li; Qian, Haifeng; Qi, Xiguang
Highlights: The protein hydrolysate of anchovy cooking wastewater (ACWWPH) was antibacterial. The liposomes were constructed from S. aureus membrane lipids. An antimicrobial peptide was targeted separated from ACWWPH by equilibrium dialysis. The peptide induced the change in cell surface hydrophobicity. The peptide had membrane-permeable action. Abstract: Anchovy ( Engraulis japonicus ) cooking wastewater (ACWW) is a by-product resulted from the production of boiled–dried anchovies in the seafood processing industry. In this study, the protein hydrolysate of ACWW (ACWWPH) was found to have antimicrobial activity after enzymatic hydrolysis with Protamex. For the targeted screening of antibacterial peptides, liposomes constructed from Staphylococcus aureus membrane lipids were used in an equilibrium dialysis system. The hydrolysate was further purified by liposome equilibrium dialysis combined with high performance liquid chromatography. The purified antimicrobial peptide (ACWWP1) was determined to be GLSRLFTALK, with a molecular weight of 1104.6622 Da. The peptide exhibited no haemolytic activity up to a concentration of 512 μg/ml. It displayed a dose-dependent bactericidal effect in reconstituted milk. The change in cell surface hydrophobicity and membrane-permeable action of the purified ACWWP1 may have contributed to the antibacterial effect. This study suggests that liposome equilibrium dialysis can be used for the targeted screening of antimicrobial peptides.